2011
DOI: 10.1155/2011/537459
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Contrasting Measurements of Microbial Dynamics in Pasture and Organic Farm Soils

Abstract: Soil bacteria exhibit short-term variations in community structure, providing an indication of anthropogenic disturbances. In this study, microbial biomass carbon (MBC), potentially mineralizable nitrogen (PMN), community level physiological profiling (CLPP), and culture-dependent DGGE (CD DGGE) fingerprinting of the 16S rRNA gene were used to compare microbial communities in organic farm and pasture soils subjected to differing agronomic treatments. Correlation analyses revealed significant relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…These conditions create an environment that supports microbes by providing active C by means of root exudates and organic nutrients from manure. The PMN revealed the capacity of the soil to supply mineralised N from SOM reserves with the aid of microbes (Edenborn et al 2011). Due to low productivity of natural fynbos species and the associated low grazing capacity of 77 ha per large stock unit (Boshoff et al 2001), the virgin soil required relatively low N levels to function in a sustainable manner, rendering the potential of the microbes to mineralise N higher in cultivated pasture soil than in the virgin soil.…”
Section: Organic Matter Indicatorsmentioning
confidence: 99%
“…These conditions create an environment that supports microbes by providing active C by means of root exudates and organic nutrients from manure. The PMN revealed the capacity of the soil to supply mineralised N from SOM reserves with the aid of microbes (Edenborn et al 2011). Due to low productivity of natural fynbos species and the associated low grazing capacity of 77 ha per large stock unit (Boshoff et al 2001), the virgin soil required relatively low N levels to function in a sustainable manner, rendering the potential of the microbes to mineralise N higher in cultivated pasture soil than in the virgin soil.…”
Section: Organic Matter Indicatorsmentioning
confidence: 99%
“…These methods are also costly and require a high level of expertise. Although only a small fraction of soil microbes is culturable [16][17][18], some researchers [19][20][21] found that culturable microbial populations could act as indicators of soil health. Olsen and Bakken [19] found that the energy flow via the non-colony forming microbial population is a very small fraction of that of the whole of the soil ecosystem, while Ellis et al [20] found that monitoring colony forming bacteria was a useful tool in determining the effect of anthropogenic actions.…”
Section: Introductionmentioning
confidence: 99%
“…Olsen and Bakken [19] found that the energy flow via the non-colony forming microbial population is a very small fraction of that of the whole of the soil ecosystem, while Ellis et al [20] found that monitoring colony forming bacteria was a useful tool in determining the effect of anthropogenic actions. Edenborn et al [21] described culturable bacteria as being useful in indicating selected agronomic disturbances as well as adding to our understanding of the link between microbes and environmental processes.…”
Section: Introductionmentioning
confidence: 99%